Magnetohydrodynamics flow of Ag-TiO2 hybrid nanofluid over a permeable wedge with thermal radiation and viscous dissipation - Kho, Yap Bing; Rahimah, Jusoh; Mohd Zuki, Salleh; Mohd Hisyam, Ariff; Nooraini, Zainuddin (Elsevier, 2023)
Hybrid nanofluids, which are made by suspending non-identical nanoparticles, have been a prominent research area because of their high efficiency in heat transfer. The analysis of the magnetohydrodynamics flow of Ag-TiO2 hybrid nanofluid over a permeable wedge with heat radiation and viscous dissipation is mathematically examined in this paper. Ordinary differential equations are deduced by applying the corresponding similarity transformations to the mathematical modelling of the governing partial differential equations. The dimensionless governing equations are solved using the built-in bvp4c function in the MATLAB package to compute the dual solutions and the stability analysis. A respectable degree of agreement has been obtained after comparing the current results with the earlier study. Prandtl number, magnetic parameter, radiation parameter, Eckert number, and other governing factors have all been studied, along with their physical impacts on fluid flow. The graphical results have been demonstrated and described in relation to the profiles of temperature and velocity distribution, skin friction as well as the Nusselt number. It has been established that the higher volume percentage of titania nanoparticles has the potential to improve thermal conductivity, and the first solution has been found to be stable in this flow.